用于调整声波谐振器的频率响应的负荷谐振器 (2023)
公开了一种声波滤波器装置(710)。该装置包括声波滤波器元件(100)以及耦合到声波滤波器元件的第一谐振器(702)和第二谐振器(712)。声波滤波器元件包括位于压电层(110)的顶表面上的叉指式的输入电极和输出电极以及在压电层的底表面上的反电极。第一谐振器和第二谐振器中的每个包括在压电层的顶表面上的谐振器电极(732，734)以及在压电层的底表面上的谐振器反电极。第一谐振器(702)在第一频率处具有谐振器阻抗中的第一陷波。第二谐振器(712)包括在第二谐振器电极(734)上的第一质量负荷层(708)，使得第二谐振器在不同于第一频率的第二频率处具有谐振器阻抗中的第二陷波。 The device includes an acoustic wave filter element, and a first resonator. The acoustic wave filter element includes interdigitated input electrodes and output electrodes located on a top surface of a piezoelectric layer and a counter-electrode on a bottom surface of the piezoelectric layer. The acoustic wave filter element provides a response with a sideband at a sideband frequency range. The first resonator includes a first resonator electrode on the top surface of the piezoelectric layer and a first resonator counter-electrode on the bottom surface of the piezoelectric layer. The first resonator has a first notch in resonator impedance at a first frequency. The first resonance frequency is tuned to fall within the sideba